Opportunities and Challenges for Development of Photovoltaic Micro-gird for User-side - WU Xiaoyun; GU Guangjuan (Kongzhi Yu Xinxi Jishu)
This paper describes the basic concept of photovoltaic micro-gird for user-side, analyzes its developing opportunities from grid parity, programming and constructing of smart-gird and architecture photovoltaic respectively, and illuminates its resistances and challenges for the development in the light of problems such as programming and constructing of power distribution network, coordination running of photovoltaic power and power distribution network, power grid stabilization and power quality.